THE EFFECT OF PURPLE EGGPLANT EXTRACT (Solanum melongena l) ON THE MOTILITY OF SPERMATOZOA - Lahdji, Aisyah; Novitasari, Andra (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Purple eggplant (Solanum melongena L.) has been proven contain alkaloid solasodin compounds that have antifertility properties, but so far scientific studies on the effects of purple eggplant on sperm motility have not been done. The aims of the study is to determine the effect of purple eggplant extract on spermatozoa motility of male rats Wistar strain. This research was an experimental research with post test only control group design. Extraction of purple eggplant used maseration method with 96% ethanol solvent. A total of 28 mice were divided into 4 groups: a control group that was given distilled water, the treatment I, II, and III were given extracts of eggplant with a dose of 175.62; 351.24; And 526.86 mg / 200 g body weight for 3 days. The motility of spermatozoa was analyzed by taking sperm samples from the cauda epididymis on day 7. Based on ANOVA test results showed that the mean spermatozoa motility between treatments there  was a significant difference (p=0,000). Control group with treatment group (Iand II) did not differ significantly (p> 0.05). The mean spermatozoa motility decreased significantly in treatment III (46,43 + 23,56) compared to control, treatment I, and treatment II. Keyword : purple eggplant; motility; spermatozoa